Blood–brain barrier disruption and angiogenesis in a rat model for neurocysticercosis - Carmen-Orozco R.P. (2019)
Neurocysticercosis (NCC) is a helminth infection affecting the central nervous system caused by the larval stage (cysticercus) of Taenia solium. Since vascular alteration and blood–brain barrier (BBB) disruption contribute to NCC pathology, it is postulated that angiogenesis could contribute to the pathology of this disease. This study used a rat model for NCC and evaluated the expression of two angiogenic factors called vascular endothelial growth factor (VEGF-A) and fibroblast growth factor (FGF2). Also, two markers for BBB disruption, the endothelial barrier antigen and immunoglobulin G, were evaluated using immunohistochemical and immunofluorescence techniques. Brain vasculature changes, BBB disruption, and overexpression of angiogenesis markers surrounding viable cysts were observed. Both VEGF-A and FGF2 were overexpressed in the tissue surrounding the cysticerci, and VEGF-A was overexpressed in astrocytes. Vessels showed decreased immunoreactivity to endothelial barrier antigen marker and an extensive staining for IgG was found in the tissues surrounding the cysts. Additionally, an endothelial cell tube formation assay using human umbilical vein endothelial cells showed that excretory and secretory antigens of T. solium cysticerci induce the formation of these tubes. This in vitro model supports the hypothesis that angiogenesis in NCC might be caused by the parasite itself, as opposed to the host inflammatory responses alone. In conclusion, brain vasculature changes, BBB disruption, and overexpression of angiogenesis markers surrounding viable cysts were observed. This study also demonstrates that cysticerci excretory-secretory processes alone can stimulate angiogenesis. © 2018 Wiley Periodicals, Inc.